2021
DOI: 10.3389/fped.2021.642369
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Patients' and Neonatologists' Satisfaction With the Use of Telemedicine for Neonatology Prenatal Consultations During the COVID-19 Pandemic

Abstract: Background: During the COVID-19 pandemic, telemedicine plays a critical role in providing safe, effective healthcare services, while reinforcing social distancing and optimizing the use of personal protective equipment. In this context, the Oklahoma Children's Hospital implemented virtual neonatology prenatal visits for pregnant women with a diagnosis of fetal anomalies. While tele-consultations have been broadly used with a high degree of acceptance in rural and remote areas, satisfaction has not been assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 17 publications
1
16
0
1
Order By: Relevance
“…An averaged mean score of ≥5 indicates that a participant demonstrates on average a slight intention to change a health behavior. This approach to determine favorable outcomes on Likert scales is in line with previous studies (Chipchase et al, 2012;Lapadula et al, 2021). Prior to performing regression analyses, we tested whether the variables met the assumptions of regression methodologies, including normally distributed residuals, linearity, and multicollinearity [based on VIF and correlations between predictors of <0.7 (Vatcheva et al, 2016)].…”
Section: Discussionmentioning
confidence: 89%
“…An averaged mean score of ≥5 indicates that a participant demonstrates on average a slight intention to change a health behavior. This approach to determine favorable outcomes on Likert scales is in line with previous studies (Chipchase et al, 2012;Lapadula et al, 2021). Prior to performing regression analyses, we tested whether the variables met the assumptions of regression methodologies, including normally distributed residuals, linearity, and multicollinearity [based on VIF and correlations between predictors of <0.7 (Vatcheva et al, 2016)].…”
Section: Discussionmentioning
confidence: 89%
“…interaction and the ability of parents to visit and participate in the care of critically ill newborns [13][14]. These changes place even greater demands on providers who operate remote healthcare service delivery systems and families of neonates who participate in them.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Rapid implementation of prenatal virtual consultation programs with mothers with fetal anomalies during the pandemic has allowed care to continue, where the providers could explain the fetal defect and formulate a care plan for the delivery room and NICU [ 50 ]. A recently conducted study showed high levels of physician and patient satisfaction with telemedicine to provide prenatal consultation during the COVID-19 pandemic, demonstrating feasibility and effectiveness for this application [ 51 ]. However, while access to care and travel burden for patients improved, issues with connectivity and video/audio quality persisted [ 50 ].…”
Section: Introductionmentioning
confidence: 99%